Designing Sound Fiscal Relations Across Government Levels in Decentralized Countries - Boadway, Robin (IMF Working Papers; Working Paper ;, 2018)
This paper discusses how decentralized countries can achieve sound fiscal relations between the central government and lower government levels. The concepts of 'vertical gap' and 'vertical balance' provide an analytical framework for identifying and addressing key challenges. These concepts can help policymakers ensure that the financing of subnational governments (composed of transfers received from the center, own revenues, and borrowing) is both efficient and adequate given the allocation of spending responsibilities. More generally, the paper offers some perspectives about the optimal design of decentralization systems by examining the sequencing and economic principles underlying revenue and expenditure assignments, the use of transfers, and borrowing.